An Empirical Analysis of Mobile Apps’ Popularity Metrics in Mobile Software Ecosystems - Gomes, Ludymila L. A.; Fontão, Awdren L.; Bezerra, Allan J. S.; Dias-Neto, Arilo C. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2016)
The growing of mobile platforms in the last years has changed the software development scenario and challenged developers around the world in building successful mobile applications (apps). Users are the core of a mobile software ecosystem (MSECO). Thus, the quality of an app would be related to the user satisfaction, which could be measured by its popularity in App Store. In this paper, we describe the results of a mapping study that identified and analyzed how metrics on apps’ popularity have been addressed in the technical literature. 18 metrics were identified as related to apps’ popularity (users rating and downloads the most cited). After that, we conducted a survey with 47 developers acting within the main MSECOs (Android, iOS and Windows) in order to evaluate these 18 metrics regarding their usefulness to characterize app's popularity. As results, we observed developers understand the importance of metrics to indicate popularity of apps in a different way when compared to the current research.